Application of 13C isotope labeling using liquid chromatography mass spectrometry (LC‐MS) to determining phosphate‐containing metabolic incorporation. (4th December 2013) - Bhowmik, Salil Kumar; Putluri, Vasanta; Kommagani, Ramakrishna; Konde, Sai Aparna; Lydon, John P.; Sreekumar, Arun; Putluri, Nagireddy
<x xml:space="preserve">Abstract</x> Here, we describe an approach wherein negative electrospray ionization mass spectrometry has used to understand the relative flux through phosphate containing metabolic intermediates associated with central carbon metabolism after administering cells with 13C‐labeled substrates. The method was applied to examine the 13C incorporation through glycolysis in T47D breast cancer cells and showed reduction of glycolytic relative flux upon treatment with 2‐Deoxyglucose. Copyright © 2013 John Wiley & Sons, Ltd.